A maize death acid, 10-oxo-11-phytoenoic acid, is the predominant cyclopentenone signal present during multiple stress and developmental conditions. (1st February 2016) - Christensen, Shawn A.; Huffaker, Alisa; Hunter, Charles T.; Alborn, Hans T.; Schmelz, Eric A.
Abstract: Recently we investigated the function of the 9-lipoxygenase (LOX) derived cyclopentenones 10-oxo-11-phytoenoic acid (10-OPEA) and 10-oxo-11, 15-phytodienoic acid (10-OPDA) and identified their C-14 and C-12 derivatives. 10-OPEA accumulation is elicited by fungal and insect attack and acts as a strong inhibitor of microbial and herbivore growth. Although structurally similar, comparative analyses between 10-OPEA and its 13-LOX analog 12-oxo-phytodienoic acid (12-OPDA) demonstrate specificity in transcript accumulation linked to detoxification, secondary metabolism, jasmonate regulation, and protease inhibition. As a potent cell death signal, 10-OPEA activates cysteine protease activity leading to ion leakage and apoptotic-like DNA fragmentation. In this study we further elucidate the distribution, abundance, and functional roles of 10-OPEA, 10-OPDA, and 12-OPDA, in diverse organs under pathogen- and insect-related stress.